2009
DOI: 10.1590/s0037-86822009000400015
|View full text |Cite
|
Sign up to set email alerts
|

Salmonelose septicêmica prolongada associada à esquistossomose: evolução do conhecimento e mecanismos imunopatogênicos

Abstract: A salmonelose septicêmica prolongada constitui entidade clínica caracterizada por febre irregular prolongada e hepatoesplenomegalia, decorrente da coinfecção por salmonelas em indivíduos com esquistossomose. O quadro clínico difere tanto das manifestações da esquistossomose isoladamente, quanto daquele associado somente à infecção por salmonelas patogênicas, resultando em uma entidade clínica individualizada 99 . QUADRO CLÍNICOA salmonelose septicêmica prolongada acomete preferencialmente jovens entre 10 e 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 96 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…These healed lesions may be totally asymptomatic, though secondary bacterial infection usually supervenes due to urological instrumentation, leading to chronic cystitis. In certain endemic areas, salmonella organisms are notorious causes of resistant secondary bacterial cystitis [4] , owing to the known symbiotic association between schistosomes and certain salmonella strains [5] .…”
Section: Fibrotic Lesionsmentioning
confidence: 99%
“…These healed lesions may be totally asymptomatic, though secondary bacterial infection usually supervenes due to urological instrumentation, leading to chronic cystitis. In certain endemic areas, salmonella organisms are notorious causes of resistant secondary bacterial cystitis [4] , owing to the known symbiotic association between schistosomes and certain salmonella strains [5] .…”
Section: Fibrotic Lesionsmentioning
confidence: 99%
“…Another study demonstrated that the host’s commensal bacteria during infection by S. mansoni played an important role in the formation of intestinal granulomas and specific immune responses of schistosomiasis, which may influence the excretion of eggs ( Barnhill et al, 2011 ). There are a few case reports related to septicemia, which demonstrated the coinfection with gut bacteria and S. mansoni ( Muniz-Junqueira, Tosta & Prata, 2009 ; Barnhill et al, 2011 ; Hsiao et al, 2016 ). Once in circulation, these gut bacteria reach the adult worms of S. mansoni present in mesenteric veins and colonize the cecum of the parasite ( Muniz-Junqueira, Tosta & Prata, 2009 ).…”
Section: Schistosomiasismentioning
confidence: 99%
“…There are a few case reports related to septicemia, which demonstrated the coinfection with gut bacteria and S. mansoni ( Muniz-Junqueira, Tosta & Prata, 2009 ; Barnhill et al, 2011 ; Hsiao et al, 2016 ). Once in circulation, these gut bacteria reach the adult worms of S. mansoni present in mesenteric veins and colonize the cecum of the parasite ( Muniz-Junqueira, Tosta & Prata, 2009 ). The association of bacteria with S. mansoni enables prolonged bacterial infections, the development of antibiotics resistance, and the ineffective treatment of both infections ( Barnhill et al, 2011 ).…”
Section: Schistosomiasismentioning
confidence: 99%
“…A study suggested that symbiotic bacteria in the host play a significant role in the formation of intestinal granulomas and the specific immune response during S. mansoni infection, which may impact the excretion of eggs. Cases of co-infection with intestinal bacteria and schistosomes have been reported, where intestinal bacteria, once in the bloodstream, can reach the adult schistosome worms residing in the mesenteric veins and establish colonization in the parasite's cecum [ 50 ]. The most frequently reported association is between Schistosoma and Salmonella infection, with most studies consistently finding that prior schistosome infections enhance and prolong subsequent Salmonella infection.…”
Section: Introductionmentioning
confidence: 99%